Law enforcement ethics classic and contemporary issues - Fitch, Brian D. (SAGE, 2014)
"This unique collection of essays covers many of the important facets of law enforcement ethics, including the selection, training, and supervision of officers. Editor Brian D. Fitch brings together the works of a diverse task force with a vested interested in reducing officer misconduct--including law enforcement scholars, educators, and practitioners from a variety of disciplines--to present a comprehensive look at this critical subject that is gaining more attention in agencies and in the media today. The text covers topics on the roles of culture, environment, social learning, policy, and reward systems as they pertain to law enforcement ethics, as well as the ethics of force, interrogations, marginality, and racial profiling. This volume also covers several unique aspects of ethics, such as the role of Post-Traumatic Stress Disorder in misconduct (PTSD), cheating during law enforcement promotional practices, off-duty misconduct, and best practices in developing countries."--Publisher's website.